4 Developing a framework to improve leadership performance in healthcare organisations: the case of the kingdom of Saudi Arabia - Algarni, Namshan; McLaughlin, Patrick; Al-Ashaab, Ahmed (BMJ Publishing Group, 2018)
In order to improve leadership performance and enhance effective leadership in the healthcare sector organisations in general and the KSA in particular, this study proposes a theoretical framework to address the way in which leadership competency strengthens the relationship between leaders and followers. This research uses a constructive-interpretive philosophical approach, applying a qualitative strategy to achieve its objectives. The study aimed to identify the factors that related to performance level, including enablers and inhibitors of performance improvement. This helped to build an initial understanding about the context of the project and hence, address the critical factors and aspects that could be influencing leadership performance improvement in the healthcare sector in Saudi Arabia in order to develop a framework with suggested interventions to improve the productivity in this vital sector. Sampling of this study is the Health affairs of the Ministry of the Saudi National Guard. NGHA has also become well known internationally, especially in successful conjoined twins separations.